Digitally Fabricated Fixed Restoration for Immediate Replacement After Extraction and Splinting the Adjacent Mobile Teeth - Jian Li; Shenghao Xue; Ke Li; Tianyi Huyan; Ting Jiang (Hindawi Limited, 2024)
Clinical Significance: This minimally invasive restorative method achieved the fixation of loose teeth while restoring the missing teeth, but the success of the treatment needed long-time observation.